The use of cynotherapy associated with physiotherapeutic intervention in the treatment of elderly with diagnosis of depression (Research, Society and Development, 2021)
As human beings age, social circles tend to shrink, people tend to become more isolated and can often develop some harmful impact on their emotional health. In this context, a pet can be a great source of joy and make a lot of difference throughout the aging process. Observing this condition, the present study aims to analyze the effects of cynotherapy (Animal Assisted Therapy) as a scientifically proven intervention, associated with the treatment of elderly people diagnosed with depression. This is a bibliographic and systematic research, encompassing studies dating from 2015 to 2019. The results analyzed show that there are few studies dealing with this topic, and most of them ask for a greater discussion of this theme, corroborating to demonstrate how much therapy with animals is healthy and brings benefits to the physical and mental health and quality of life of the elderly.